2010
DOI: 10.1002/jso.21515
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of malignant melanoma

Abstract: Even though there is an epidemic of malignant melanoma occurring in the United States, it appears that patients are being diagnosed earlier with thinner lesions that are capable of being cured with simple surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This finding, too, is in line with recent international population studies. [5][6][7] The decrease in melanoma thickness is related to a sharp increase in the diagnoses of thin melanomas (which increased by 244 and 132% from 1985-1989 to 1995-1999 and from 1995-1999 to 2005-2009, respectively) compared with melanomas >2 mm in thickness (increases of 82 and 36%, respectively, in the same two periods) (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding, too, is in line with recent international population studies. [5][6][7] The decrease in melanoma thickness is related to a sharp increase in the diagnoses of thin melanomas (which increased by 244 and 132% from 1985-1989 to 1995-1999 and from 1995-1999 to 2005-2009, respectively) compared with melanomas >2 mm in thickness (increases of 82 and 36%, respectively, in the same two periods) (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
“…Female prevalence is frequently observed in European studies whereas the gender ratio is often more equal in US studies. 5,7,9 We can speculate that this result may be due to different types of population, race and sun-exposure behaviour. When we analysed the data for associations between gender and mean lesion thickness we found that for lesions Յ2 mm thick, women were more prevalent than men; hence the diagnosis of thin lesions increased in time in the same manner for both sexes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…34 Thin melanomas are generally associated with a good prognosis; however, survival is variable as 20% are associated with metastasis and 5% prove to be fatal. 35 Notably, recent studies have shown that nearly all the thin melanomas that develop metastases are ≥ 0.75 mm in thickness.…”
Section: Lymphatic Invasion and Metastasismentioning
confidence: 99%
“…4 In the United States, Europe, and Australia, the majority of patients with newly diagnosed cutaneous melanomas have thin tumors. [5][6][7][8] Therefore, even though fewer than 10 % of patients with thin melanomas will eventually progress, this population constitutes a large number of individuals. It is clearly important to identify these higher-risk patients early in the course of their disease if possible, so that management plans appropriate for the biologic aggression of their tumors can be initiated.…”
mentioning
confidence: 99%